Motor Skills and Cognitive Development: A Study on the Impact of Physical Activity on Children's Learning - Suci Aprilyati Ruiyat (CV Kalimasada Group, 2025)
This study aims to examine the impact of physical activity on motor skills and cognitive development in children. While physical activity is essential for physical growth, it also plays a significant role in cognitive development. This study explores the relationship between motor skill enhancement and children's learning abilities in the context of primary education. The study found that structured physical activity improves motor skills, which in turn contributes to better cognitive functions such as attention, working memory, and problem-solving abilities. These findings suggest the importance of incorporating physical activity into the curriculum to support holistic child development.